Synthesis, structural diversification, biological activities and biotransformation of dibenzylacetones : simple chemistry furnishing potent compounds - Din, Zia Ud (2016)
The structural diversity of known compounds holding two benzene rings directly connected to each other (Bis-phenyl), or separated by a carbon-chain (Bisarylalkane), is nowadays generated intensive scientific studies across the world. Some of them are very renowned for their important biodynamic activities for human beings. For instance, the natural occurring classes of substances Stilbene (Bis-arylethene), Chalcone (Bis-arylpropenone) and Curcumin (Bis-arylheptene) have been subject of deep studies in literature due to their pharmacological activities such as antimicrobial, anti-inflammatory, anti-tumor, antioxidant and anticancer. Almost all of these compounds have in common the amino acid phenylalanine as biosynthetic precursor. In this work, we seek to give a concise overview of their structures diversity, occurrence, chemistry and the bioactivities of dibenzylacetones established. The effort to synthesize these compounds and their congeners and its modification with good pharmaceutical profile were carried. We have studied the anti-parasitic activity of all these synthesized compounds and found some potent compounds. The mechanistic study show that enzyme inside parasite reduces the C=C bonds in synthesized dibenzylacetones and leading to more potency which alter redox system of parasite, which result increase of nitrogen and oxygen species and interfere mitochondria function, which ultimately causes death of parasite. Although the literature contains only limited computational studies on these compounds, it can be predicted good and differential π-π interactions of aromatic rings of these compounds with aromatic amino acids in enzymes. We have made an effort to explain our results in the result of docking and DFT analysis.